Cellulose and nanocellulose-based flexible-hybrid printed electronics and conductive composites – A review. (15th October 2018) - Agate, Sachin; Joyce, Michael; Lucia, Lucian; Pal, Lokendra
Highlights: Significant market opportunities for biopolymers in flexible-hybrid printed electronics. High smoothness and transparency can be achieved with TEMPO oxidation/nanocellulose. Doping or ionizable grafting is required for conductivity in cellulose. Grafted negative charged side chains on cellulose can help in positive ion conduction. Nanocellulose shows piezoelectric properties due to crystalline asymmetry. Abstract: Flexible-hybrid printed electronics (FHPE) is a rapidly growing discipline that may be described as the precise imprinting of electrically functional traces and components onto a substrate such as paper to create functional electronic devices. The mass production of low-cost devices and components such as environmental sensors, bio-sensors, actuators, lab on chip (LOCs), radio frequency identification (RFID) smart tags, light emitting diodes (LEDs), smart fabrics and labels, wallpaper, solar cells, fuel cells, and batteries are major driving factors for the industry. Using renewable and bio-friendly materials would be advantageous for both manufacturers and consumers with the increased use of (FHPE) electronics in our daily lives. This review article describes recent developments in cellulose and nanocellulose-based materials for FHPE, and the necessary developments required to propagate their use in commercial applications. The aim of these developments is to enable the creation of FHPE devices and components made almost entirely of cellulose materials.